2012
DOI: 10.4172/2155-6156.1000231
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Camel Milk and Ginkgo biloba Extract Against Alloxan-Induced Diabetes in Rats

Abstract: Diabetes Mellitus is one of the most important health problems worldwide, indicating high prevalence and mortality. In recent years, Ginkgo biloba extract has become a subject of interest because of its beneficial effects on human health, also camel milk has a good nutritive value, in addition to its antigenotoxic and anticytotoxic effects. Therefore the purpose of the present study was to investigate the protective and curative effects of camel milk and Ginkgo biloba extract against alloxan-induced diabetes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
5
5
0
Order By: Relevance
“…As a consequence, it provokes damage in structural and functional integrity of hepatic tissue, as evidenced by increase in the oxidative deterioration of lipids in the cellular membrane (Schmatz et al, ). A decrease in enzymatic and non‐enzymatic antioxidant system was observed in this present study, in agreement with previous reports in alloxan‐induced diabetes (Hassan & Eman, ). One possible mechanism for the reduction may be the inactivation caused by excessive amounts of free radicals after persistent hyperglycemia in diabetic patients (Rains & Jain, ).…”
Section: Discussionsupporting
confidence: 93%
“…As a consequence, it provokes damage in structural and functional integrity of hepatic tissue, as evidenced by increase in the oxidative deterioration of lipids in the cellular membrane (Schmatz et al, ). A decrease in enzymatic and non‐enzymatic antioxidant system was observed in this present study, in agreement with previous reports in alloxan‐induced diabetes (Hassan & Eman, ). One possible mechanism for the reduction may be the inactivation caused by excessive amounts of free radicals after persistent hyperglycemia in diabetic patients (Rains & Jain, ).…”
Section: Discussionsupporting
confidence: 93%
“…This increase in TG might be due to the shortage of insulin under diabetic condition. The obtained result came in agreement with those of Arkkila et al 2001, Hassan & Emam, 2012and Isa et al, (2013. These results are in agreement with previous reports (Hassan & Emam, 2012;and Isa et al, 2013) and in the data presented in figure (1).…”
Section: Biochemical Analyses: Serum Biochemical Analysessupporting
confidence: 93%
“…It also inhibits glucose-induced insulin secretion through its ability to inhibit the beta cell glucose sensor, glucokinase. 47 In this study, alloxan was found to cause a significant reduction in the body and organs weights of rats when compared with the control. Animals receiving ICPAE increased their body and organs weights compared to that of the diabetic rats.…”
Section: Discussionmentioning
confidence: 60%
“…Pancreatic beta cells were destroyed using alloxan, a toxic glucose analogue that accumulate in pancreatic beta cells via glucose transporter 2 (GLUT2). It also inhibits glucose‐induced insulin secretion through its ability to inhibit the beta cell glucose sensor, glucokinase …”
Section: Discussionmentioning
confidence: 99%